2003
DOI: 10.1139/f03-041
|View full text |Cite
|
Sign up to set email alerts
|

A simulation model for designing groundfish trawl surveys

Abstract: This paper describes a convenient simulation model, based on the compound binomial-gamma distribution, to assist the planning and design of groundfish trawl surveys. The analysis uses swept-area density measurements from stratified tows to give a simple nonparametric biomass estimate. A parametric simulation model requires only three input parameters for each stratum, which can be estimated initially from past surveys or commercial fishery data. Analytical results provide intuitive algorithms for estimating va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Our analysis showed that stratifying by habitat features including reef structure, rugosity, and depth was effective in partitioning the spatial heterogeneity of reef-fish density, and thus contributed to increased sampling efficiency; however, there may be room for future improvement to this stratification scheme. Analytical investigations of how specific biotic and abiotic factors may be configured to comprise strata that better delineate low, moderate, and high variance regions may yield significant improvements in design performance (Schnute and Haigh, 2003). Treating juveniles and adults of the same species as separate biological entities with respect to stratification also contributed to design efficiency by accounting for potential changes in spatial distribution patterns at the onset of reproductive maturity.…”
Section: Stock Assessmentmentioning
confidence: 99%
“…Our analysis showed that stratifying by habitat features including reef structure, rugosity, and depth was effective in partitioning the spatial heterogeneity of reef-fish density, and thus contributed to increased sampling efficiency; however, there may be room for future improvement to this stratification scheme. Analytical investigations of how specific biotic and abiotic factors may be configured to comprise strata that better delineate low, moderate, and high variance regions may yield significant improvements in design performance (Schnute and Haigh, 2003). Treating juveniles and adults of the same species as separate biological entities with respect to stratification also contributed to design efficiency by accounting for potential changes in spatial distribution patterns at the onset of reproductive maturity.…”
Section: Stock Assessmentmentioning
confidence: 99%
“…only one seasonÕs harvest data). Initial estimates of abundance of age-2 yellow perch since the year 2000 were higher than the subsequent estimate by an average of 13% (Yellow Perch Task Group 2001, 2002, 2003, 2004, 2005, 2006, 2007. Since 2002, first estimates have been higher than the subsequent estimate by 30%.…”
Section: Discussionmentioning
confidence: 93%
“…Sampling regimens that consider the biology and ecology of the target species, and that are adaptable as fish communities and ecology change are critical to effective fisheries management (Smith & Gavaris 1993; McAllister & Pikitch 1997; Folmer & Pennington 2000; Schnute & Haigh 2003). An inappropriate sampling regimen can produce variable and biased estimates of fish abundance (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 4a, improved stratification (and thus more informed partitioning of spatial variance) can improve survey efficiency, resulting in a downward and leftward shift of precision-sample size curves. An initial full-frame survey would provide the fundamental data for refining the stratification scheme using principles of resource selection theory and other analysis techniques for evaluating animal use of habitats (Steffánsson 1996;Manly et al 2002;Schnute and Haigh 2003). These analyses would focus on identifying improved abiotic and biotic environmental variables (e.g., habitat complexity, patchiness, benthic cover, etc.)…”
Section: Discussionmentioning
confidence: 99%